ANALISIS FAKTOR TERJADINYA PREEKLAMPSIA PADA IBU HAMIL - Hasriani, Hasriani; Nirmalarumsari, Chrecencya; Novia Arini, Ketut; Tasripin, Mellysa Wulandari (Ensiklopedia of Journal, 2025)
Preeclampsia is a pregnancy complication that has the potential to harm both the mother and the fetus, and is clinically characterized by an increase in blood pressure above normal limits. The purpose of this study was to analyze the factors associated with preeclampsia in pregnant women. A cross-sectional study design was used in this study. The study was conducted in the working area of the Marawola Community Health Center. The study was conducted in October 2024. The population consisted of all pregnant women with preeclampsia in the working area of the Marawola Community Health Center. The sample consisted of 40 respondents. The sampling technique used simple random sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results showed a relationship between the age of the pregnant woman (p-value: 0.00) and gravida (p-value: 0.00) with the occurrence of preeclampsia. It is recommended that health centers implement health promotion programs such as counseling on the dangers and ways to prevent complications that can occur during pregnancy. Women of childbearing age should also be given counseling on controlling hypertension that can occur during pregnancy by explaining the factors that can cause hypertension in pregnancy (preeclampsia). Keywords: Gravida, Pregnant Women, Preeclampsia.